2008
DOI: 10.1615/jwomenminorscieneng.v14.i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration as a Means to Building Capacity: Results and Future Directions of the National Girls Collaborative Project

Abstract: The purpose of the National Girls Collaborative Project is to extend the capacity, impact, and sustainability of existing and evolving girl-serving STEM projects and programs. This paper describes the underpinnings and design of the National Girls Collaborative Project (NGCP) and posits that the structured collaboration framework this organization foments may be a necessary component for our fi eld to move beyond our current levels of representation of women in science, technology, engineering, and mathematics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Various studies show that the collaboration activities which are carried out take place through a wide range of areas and repeated relationships due to the needs of the students. In this study, the findings obtained through three different approaches have verified this as well ( [58], [62], [83]). In the study, the collaboration relationship network between the educational organizations at the city center have been analyzed in-depth and the collaboration activities carried out in ten different subjects and the collaboration levels have been analyzed by revealing both the whole network's structural characteristics and the individual network relationships.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Various studies show that the collaboration activities which are carried out take place through a wide range of areas and repeated relationships due to the needs of the students. In this study, the findings obtained through three different approaches have verified this as well ( [58], [62], [83]). In the study, the collaboration relationship network between the educational organizations at the city center have been analyzed in-depth and the collaboration activities carried out in ten different subjects and the collaboration levels have been analyzed by revealing both the whole network's structural characteristics and the individual network relationships.…”
Section: Resultssupporting
confidence: 77%
“…According to Slater and Ravid [75], collaboration takes place in various areas such as sharing of information and sources between schools and other organizations, consultation, support, solidarity, activities related to school developmentreforms and sharing of views. In the evaluation carried out by Marra, Peterson and Britsch [62] of the national project on the development of collaboration among girls, it has been stated that collaboration between all social organizations and project partners in the realization of projects can be used as a lever and a collaboration model has been suggested. As it can be seen, schools' collaboration relationships with their environments take place in various subjects and manners.…”
Section: Inter-organizations Collaboration and Social Network Theory mentioning
confidence: 99%
“…Future research should also investigate how to extend scaffolding's reach to benefit underrepresented groups in STEM, a very important goal (Ceci, Williams, & Barnett, 2009;Syed, Azmitia, & Cooper, 2011;Thoman, Smith, Brown, Chase, & Lee, 2013). This could be pursued through a combination of strategies: look at the differences between scaffolds that work well among underrepresented groups, and those that are not as effective, examine the literature on designing effective instructional supports for members of underrepresented groups (Cuevas, Fiore, & Oser, 2002;Marra, Peterson, & Britsch, 2008), examine the literature on universal design for learning (Rao, Ok, & Bryant, 2014;Scott, Mcguire, & Shaw, 2003), and examine whether there are differences in how students from underrepresented groups are using scaffolds that could explain lower effectiveness (Belland & Drake, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Further research is needed to examine how to design and deploy computer-based scaffolding so as to increase its efficacy among underrepresented groups. There may also be a need to develop versions of scaffolds that draw on strategies known to be effective among the underrepresented groups (Cuevas et al, 2002;Lynch, 2001;Marra et al, 2008). It is clear from the literature that this is possible, as some studies have shown that specific scaffolds are more effective among lower-achieving and lower-SES middle school students than among higher-achieving and average-to-higher-SES students (Belland et al, 2011;Belland, Gu, Armbrust, et al, 2015;Belland, Gu, Kim, et al, 2015).…”
Section: Results From the Meta-analysismentioning
confidence: 99%